2020
DOI: 10.1186/s12937-020-00580-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of the dietary patterns with the risk of non-alcoholic fatty liver disease among Iranian population: a case-control study

Abstract: Background: Diet-based recommendations can be developed for preventing and treating non-alcoholic fatty liver disease (NAFLD) after investigating the effects of whole diets on NAFLD. The aim of this study was to identify major dietary patterns and their association with the risk of NAFLD. Methods: A total of 244 individuals (122 NAFLD patients and 122 controls) participated in this case-control study. The patients with NAFLD were diagnosed by a gastroenterologist. The participants' dietary intake data were col… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Our findings are consistent with those of previous studies that reported a beneficial effect of the prudent dietary pattern on NAFLD risk 26 27. The prudent pattern, similar to the dietary guidelines for Americans, was characterised by high consumption of green and yellow vegetables, light-coloured vegetables, kimchi, mushrooms, potatoes, beans, tofu, soymilk and fish.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with those of previous studies that reported a beneficial effect of the prudent dietary pattern on NAFLD risk 26 27. The prudent pattern, similar to the dietary guidelines for Americans, was characterised by high consumption of green and yellow vegetables, light-coloured vegetables, kimchi, mushrooms, potatoes, beans, tofu, soymilk and fish.…”
Section: Discussionsupporting
confidence: 91%
“…In nine out of ten collected studies–in two prospective studies[ 52 , 53 ], four case-control studies[ 33 , 54 - 56 ], and three cross-sectional studies[ 57 - 59 ], a healthy dietary pattern was associated with a decreased risk of NAFLD independent of several confounders added to the models. Moreover, in a study by Chung et al [ 60 ] “simple meal pattern” characterized by a high intake of root and yellow vegetables, fruits, dairy products, eggs and nuts also exhibited an inverse correlation with NAFLD.…”
Section: Associations Between Dietary Patterns and Risk Of Nafldmentioning
confidence: 99%
“…On the other hand, some studies report significant associations of this diet with the risk of NAFLD[ 58 , 60 ]. In the literature, the following dietary patterns familiar to the western patterns are also present: Fast food[ 54 , 55 ]; animal food/high protein[ 53 , 54 ]; red meat and alcohol[ 62 ]; high-salt[ 57 ]; high-fat dairy and refined grains[ 62 ]; high-carbohydrate/sweet/sugar/high fruits[ 53 , 64 , 65 ]; as well as, snacks and energy-dense dietary pattern[ 58 , 59 , 62 ]. The majority of these dietary patterns increased the risk of NAFLD.…”
Section: Associations Between Dietary Patterns and Risk Of Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…Food items included in the FFQ were grouped into 27 different categories according to similarities in nutrient contents and available data ( 19 , 25 27 ) for factor analysis in our study. Some food items were considered separately because their nutrient content was unique (e.g., eggs, condiments, salt, tea, coffee).…”
Section: Methodsmentioning
confidence: 99%